(3GdEJMGa HMOjK aVd GdGfUGas - (3eMeO Hf YHO Gddg Hf eMeO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf,J (B842 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3GNHQfG GdTjN GdeSfO GdCUjd CHh GdeMGSf jhSa Hf YKeGf Hf YeQ Hf eSde GdYhai HbQGAJi Ydjg HUGdMjI OeTb s
(3BNQgG (B:s
(3hef HYah ePgH dPfhfHG ehef YeQfG HGdNjQ aGNJe ChGNQg s
(3HgG fXGe GdJYbjHs
(3cJHJ HNW Cged ajg GdfbW CMjGfkGs
(3fbdJ Yf fSNI HNW GdeDda hYdi MGTjI fSNJfG gPg SeGY heYGQVI hHBNQgG SeGY SfI (B836 (3Ydi GdeDda ef YOI YdeGA efge GdfGSN faSg hTgO GdeDda Ydi gPG GdSeGY hELGRI HNWg hjdGMX Cf UaMg GdZdGa HNW GdeDda s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs